"Das Ding": Excessive Existence: Discussion of "Melancholic Psychosis". Issue 4 (4th July 2018) - Straker, Gillian
Abstract : Derek Hook's (this issue) excellent paper provides illustrations of complex Lacanian concepts through the relatively rare presentation of Lacanian case material. His paper lends itself to reading Freud with Lacan. This reply to his paper engages such a reading to show that the idea of the over present object emphasised by Lacan is prefigured in Freud in his 1917 paper on Mourning and Melancholia. My reply to Hook affirms the additional clinical themes he introduces and indicates that these themes would be anticipated if, as Lacan argues, melancholia is seen to be underpinned by a psychotic structure. Finally, the reply argues for a resurrection of the Lacanian notion of Das Ding, as it connotes differently to objet a despite overlaps in meaning and the fact that in later Lacan the term Das Ding was dropped.